Structure and evolution of basin and petroleum systems within a transformrelated passive margin setting : data-based insights from crust-scale 3D modelling of the Western Bredasdorp Basin, offshore South Africa - Sonibare, Wasiu Adedayo (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.